The bidirectional relationship between activities of daily living and frailty during short-and long-term follow-up period among the middle-aged and older population: findings from the Chinese nationwide cohort study - Li, Xiaoping; Li, Xiaoguang; Sun, Lu; Yang, Liu; Wang, Congzhi; Yuan, Ting; Lei, Yunxiao; Li, Jing; Liu, Mingming; Zhang, Dongmei; Hua, Ying; Liu, Haiyang; et al. (Frontiers in Public Health, 2024)
Objective: Frailty and activities of daily living (ADL) disability are common conditions among older population. Studies on the bidirectional relationship between frailty and ADL are limited. The current study examined the cross-sectional and longitudinal associations between frailty and ADL in middle-aged and older Chinese individuals. Methods: The data was collected through the China Health and Retirement Longitudinal Study (CHARLS), conducted in 2011, 2013, and 2015, encompassing 17,284 individuals aged ≥ 45 years. We excluded individuals without follow-up data. 2631 participants finished the baseline survey. The definition of ADL disability encompasses difficulty in engaging in either basic activities of daily living (BADL) or instrumental activities of daily living (IADL). Frailty was assessed according to the Fried criteria. Logistic regression was utilized to examine odds ratios (ORs) and 95% confidence intervals (CIs) for assessing the cross-sectional relationships between ADL with frailty at baseline. The prediction effects were explored using Cox proportional hazards analysis, testing hazard ratios (HRs) and 95%CIs. Results: In cross-sectional analysis, BADL (OR = 6.660 (4.519-9.815)), IADL (OR = 5.950 (4.490-7.866)), and ADL (OR = 5.658 (4.278-7.483)) exhibited significant associations with frailty; frailty demonstrated significant associations with BADL (OR = 6.741 (4.574-9.933)), IADL (OR = 6.042 (4.555-8.016)) and ADL (OR = 5.735 (4.333-7.591)). In longitudinal analysis, IADL and ADL were significantly associated with frailty in participants without baseline frailty in the short-term period (IADL: HR = 1.971 (1.150-3.379), ADL: HR = 1.920 (1.146-3.215)), IADL exhibited a significant association with frailty in the long-term period (HR = 2.056 (1.085-3.895). There was no significant link observed between frailty and an elevated risk of disability onset in BADL, IADL and ADL during the short-term period. When considering the long-term perspective, frailty exhibited a significant association with an elevated risk of disability onset in BADL (HR = 1.826 (1.126-2.939)) and IADL (HR = 1.724 (1.103 -2.694)). Conclusion: In middle-aged and older adults, ADL and IADL disability predicted frailty after 2-year follow-up, IADL disability predicted frailty after 4-year follow-up. Moreover, frailty did not predict BADL, IADL and ADL disability after 2-year follow-up. However, frailty predicted BADL and IADL disability after 4-year follow-up.